2012
DOI: 10.1007/s00592-011-0364-z
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of glutamate in the current diabetes epidemic

Abstract: In the present article, we propose the perspective that abnormal glutamate homeostasis might contribute to diabetes pathogenesis. Previous reports and our recent data indicate that chronically high extracellular glutamate levels exert direct and indirect effects that might participate in the progressive loss of β-cells occurring in both T1D and T2D. In addition, abnormal glutamate homeostasis may impact all the three accelerators of the "accelerator hypothesis" and could partially explain the rising frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 244 publications
(260 reference statements)
3
33
0
3
Order By: Relevance
“…Systemic plasma glutamate levels are elevated in several diseases that are characterized by oxidative stress and inflammation4, such as obesity31. Our data showed that plasma glutamate levels were elevated in diabetic patients and diabetic mice.…”
Section: Discussionsupporting
confidence: 49%
“…Systemic plasma glutamate levels are elevated in several diseases that are characterized by oxidative stress and inflammation4, such as obesity31. Our data showed that plasma glutamate levels were elevated in diabetic patients and diabetic mice.…”
Section: Discussionsupporting
confidence: 49%
“…High concentration of glutamic acid is toxic for β-cells. Excessive dietary intake of glutamate may cause obesity and insulin resistance [10]. Low levels of glycine are the result of insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Glutamate at high levels is well known to be toxic to the central nervous system [55], retinal neurons [56] and pancreatic islets [57]. As the fetal blood brain barrier is relatively permeable, even a slight increase in circulating glutamate has been shown to overstimulate neurons in the arcuate nucleus that can lead to metabolic dysregulation in later life [58].…”
Section: Discussionmentioning
confidence: 99%